Antenatal diagnosis of large sacro-coccygeal teratoma with foetal cardiomegaly and hydrops - Gupta, N; Shah, D; Singh, U; Tiwari, A (Kathmandu University Medical Journal, 2009)
We report the case of a young primigravida who presented with a 20 weeks pregnancy with a previous diagnosis of uterine fibroid. However, ultrasound evaluation revealed the presence of a large sacro-coccygeal teratoma in the foetus which was heterogeneous with cystic areas and calcific foci, and showed increased vascularity. There was also evidence of foetal cardiomegaly and hydrops foetalis, indicated by subcutaneous oedema in the foetus, thickened placenta and polyhydramnios. The presence of hydrops with sacro-coccygeal teratoma has a grave prognosis for the mother and child; hence termination of pregnancy was done. A 20 weeks old foetus with a huge sacro-coccygeal mass, which was ruptured at many places and showed areas of active bleed, was expelled. doi: 10.3126/kumj.v6i3.1717 Kathmandu University Medical Journal (2008), Vol. 6, No. 3, Issue 23, 383-385